Social entrepreneurship research in Asia-Pacific: perspectives and opportunities. Issue 1 (6th February 2017) - Sengupta, Subhanjan; Sahay, Arunaditya
Abstract : Purpose: This paper aims to facilitate researchers, academicians and entrepreneurs gain insights on the social entrepreneurship concept and future research opportunities in the context of the Asia-Pacific countries (APAC). Design/methodology/approach: The diversity of social entrepreneurship phenomenon visible in 101 journal publications was reviewed and analyzed to identify research perspectives and opportunities, with special focus on papers published on the APAC context between 1998 and 2015. The keywords for search were "social entrepreneurship", "social enterprises", "social entrepreneur" and the names of all countries in APAC. Findings: The study identifies three prominent themes in need of more research in the APAC countries: contextual, institutional and personal factors surrounding social entrepreneurship; usage of market orientation by social enterprises to generate economic and social value; and impact of social entrepreneurship education on generating talent pool for social enterprises. Originality/value: During the review on the social entrepreneurship concept, it was felt that most research originated from both sides of the Atlantic rather than the APAC. Interestingly, no review was found on research published on social entrepreneurship as perceived and practiced in APAC. Therefore, this paper would be of particular value to any researcher who would conduct social entrepreneurship research in the Asia-Pacific context. Asia-Pacific offers immense scope for empirical research for theory generation and theory testing in different contexts.